Efeito hiperalgésico produzido pela administração de bradicinina na amígdala de ratos - Dalmolin, Gerusa Duarte (2006)
The peptide bradykinin is one of the most potent algogenic substances and its role in nociception has been intensively studied in the peripheral nervous system. However, its action in pain transmission in central nervous system remains unclear. In this work, we studied the action of this peptide into amygdala, a limbic structure highly involved on pain modulation, in the thermal noxious threshold of rats. Administration of bradykinin (0.025-0.5 nmol/site) into right amygdala of rats promoted a thermal hyperalgesia, verified by a reduction in paw withdrawal latency produced by noxious heat, only in the ipsilateral paw. The hyperalgesic effect of bradykinin (0.25 nmol/site) was not due to an unspecific effect on locomotor activity, visualized on open-field test. The hyperalgesia induced by intra-amygdala injection of bradykinin (0.25 nmol/site) was abolished by co-administration of this peptide with the B2 receptor antagonist Hoe 140 (5 pmol/site), but not by its co-administration with the B1 receptor antagonist des- Arg9-[Leu8]-bradykinin (0.05 nmol/site). This hyperalgesic effect was also inhibited by co-administration of bradykinin (0.25 nmol/site) with the glutamatergic NMDA antagonist MK-801 (5 nmol/site), with the cyclooxygenase inhibitor indomethacin (10 nmol/site) or with the glial metabolic inhibitor fluorocitrate (1 nmol/site) into amygdala of the rats. The results showed that intra-amygdalar administration of bradykinin induces pain sensitization through the release of cyclooxygenase products and the activation of NMDA and B2 receptors present in amygdala s neurones and glia. These findings provide evidence that bradykinin participates of the central pain-modulating circuit.